Hertfordshire circa 1840-45 / drawn & engraved by J. Archer. - Archer, J. (Jonathan Sheppard Books, 1900)
Facsimile reprint of an 1840's map of Hertfordshire in England. It shows landforms, drainage, cities, roads and railroads. The shire's internal division into 8 hundreds is also shown.